PENTINGNYA SINTAKSIS DALAM PEMBENTUKAN KALIMAT YANG EFEKTIF - Nainggolan, Kristina Natalia Febrina; Simanjuntak, Hotma (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
Syntax is a branch of linguistics that studies sentence structure and how language elements relate to each other to form meaning. Language errors are often found in everyday life, including those found in final projects or theses. This study aims to explore the importance of syntactic understanding in constructing effective sentences, especially in the context of education. This research employs a qualitative method with a descriptive approach. Data were collected through content analysis of books, journal articles, and relevant previous studies from the last five years, and analyzed using syntactic analysis methods. The findings show that errors in syntactic structure often hinder clear and efficient communication. Common syntactic errors include the misuse of auxiliary verbs, improper sentence structure, and inappropriate word choice. This study concludes that a strong understanding of syntax is essential for constructing effective sentences, particularly in educational contexts, and efforts are needed to enhance syntactic competence.